العلوم اللسانية في علاقتها بالفكر التربوي والتعليميات - قاضي، صفية (جامعة البليدة 2 علي لونيسي - كلية الآداب واللغات, 2021)
عرفت العلوم اللسانية خاصة التطبيقية منها تطورات كبيرة في جانبها النظري والتطبيقي، وذلك نتيجة تفاعلها وتقاطعها مع مختلف العلوم الإنسانية التي تتشارك معها في الاهتمامات المعرفية نفسها، ولعل تعليمية اللغات أكثر هذه الحقول اللسانية تأثرا بالعلوم الأخرى وتأثيرا فيها، ويعد البحث في مجالات التقارب والتقاطع بين العلوم من صميم البحث العلمي، وهو يعود بالنفع على هذه العلوم في حد ذاتها بما يسهم في تطورها ورقيها، ومن ذلك البحث في طبيعة العلاقة بين العلوم اللسانية والفكر التربوي والتعليميات ومجالات التأثير والتأثر بينها، وبيان مدى استفادتها من بعضها البعض، وهو ما يهدف هذا البحث للكشف عنه وكذا عن بروز اللسانيات التربوية كميدان مشترك بين هذه العلوم. Linguistic sciences, especially applied sciences, have known major developments in their theoretical and applied aspects, as a result of their interaction and intersection with various human sciences with which they share the same cognitive interests, and perhaps teaching languages is the most affected of these linguistic fields by other sciences end is influential in them, and research is in the areas of convergence and intersection between sciences. It is at the core of scientific research, and it is beneficial to these sciences in and of itself, which contributes to their development and advancement, including researching the nature of the relationship between Linguistic sciences, educational thought, and instructional fields of influence and influence between them, and the extent to which they benefit from each other, which is what this research aims to reveal. About it and the emergence of educational linguistics as a common field between these sciences.
Keywords: المحتوي التعليمي -- العملية اللغوية -- الطرائق التدريس